Towards a Human Rights-Based Approach to Ethical AI Governance in Europe - Lasek-Markey, Marta; Hogan, Linda (My University, 2024)
As AI-driven solutions continue to revolutionise the tech industry, scholars have rightly cautioned about the risks of ‘ethics washing’. In this paper, we make a case for adopting a human rights-based ethical framework for regulating AI. We argue that human rights frameworks can be regarded as the common denominator between law and ethics and have a crucial role to play in the ethics-based legal governance of AI. This article examines the extent to which human rights-based regulation has been achieved in the primary example of legislation regulating AI governance, i.e., the EU AI Act 2024/1689. While the AI Act has a firm commitment to protect human rights, which in the EU legal order have been given expression in the Charter of Fundamental Rights, we argue that this alone does not contain adequate guarantees for enforcing some of these rights. This is because issues such as EU competence and the principle of subsidiarity make the idea of protection of fundamental rights by the EU rather than national constitutions controversial. However, we argue that human rights-based, ethical regulation of AI in the EU could be achieved through contextualisation within a values-based framing. In this context, we explore what are termed ‘European values’, which are values on which the EU was founded, notably Article 2 TEU, and consider the extent to which these could provide an interpretative framework to support effective regulation of AI and avoid ‘ethics washing’. Keywords:
PUBLISHED
Keywords: Ethics, AI governance, human rights, AI regulation, fundamental rights, ethics washing; Digital Humanities; AI Regulation; ETHICS OF AI; law and technology; Other; Globalization; Legislation